2017
DOI: 10.1159/000477466
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Resolution 3D Magnetic Resonance Imaging to Quantitatively Analyze the Shape of Eyeballs with High Myopia and Provide Assistance for Posterior Scleral Reinforcement

Abstract: Purpose: To quantitatively analyze the shape of eyes with high myopia and provide assistance for posterior scleral reinforcement (PSR) using high-resolution three-dimensional (3D) magnetic resonance imaging (MRI). Method: In all, 260 eyes of 134 patients with high myopia were assessed in this study; 120 emmetropic volunteers were enrolled as a control group. The subjects were examined using 3D T2-weighted CUBE sequences. Results: The eyeballs' axial, horizontal, and vertical lengths were longer and their volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(29 reference statements)
0
9
1
Order By: Relevance
“…Intriguingly, although LT was not associated with myopia in a previous study [34], we detected a significant difference in LT between the high myopic group and the emmetropic group in this study and in another study using the IOLMaster 700 [17]. High myopic eyes are more susceptible to zonular failure [12,35]; therefore, we suspect that the reduction in LT with longer AL can be attributed in part to zonular weakness. Zonular failure may cause the lens to sink, which will affect the accurate measurement of LT.…”
Section: Discussioncontrasting
confidence: 47%
“…Intriguingly, although LT was not associated with myopia in a previous study [34], we detected a significant difference in LT between the high myopic group and the emmetropic group in this study and in another study using the IOLMaster 700 [17]. High myopic eyes are more susceptible to zonular failure [12,35]; therefore, we suspect that the reduction in LT with longer AL can be attributed in part to zonular weakness. Zonular failure may cause the lens to sink, which will affect the accurate measurement of LT.…”
Section: Discussioncontrasting
confidence: 47%
“…Khokhar et al suggested that the anterior and posterior segments of the eye with low myopia or ametropia were proportional to eye growth but disproportionate in high myopia (Khokhar et al, 2018). Research using 3D MRI of myopia morphology also found that the longitudinal and transverse diameter ratio of the eyeball was larger in high myopia than in non-high myopia (Wen et al, 2017). This suggested that the expansion of the eyeball was uneven in SEE as compared to MEE.…”
Section: Discussionmentioning
confidence: 99%
“…The method for 3D MRI scanning has been described in our previous studies. 10 Briefly, a magnetic resonance scanner and 32-channel head coil were used while the patient was in a supine position. After closing the eyelid, the 3D sequence MRI scanning of the eye was applied.…”
Section: Methodsmentioning
confidence: 99%